La promesa de compra venta de bienes inmuebles en el marco normativo ecuatoriano - Sisa Pacari, Jorge Amable (2015)
The promise’s contract of real estate in the Ecuadoran legislation is a fundamental and indispensable instrument in the economic, juridical and social relation between persons, for which, it result evident and necessary to review the regulation and its application in the Ecuadoran right. In the courts and rooms of justice administration, an alarming number of demands exist for breach or inefficiency of the promise’s contract buying and selling of real estate, which obeys own factors of the contracting party and the nonobservance or ignorance of the Law. Result evident to examine: if the bad use and the breach of the promise of buying and selling, obeys a bad structure and legal regulation of the promise’s contract of buying and selling. In the Ecuadoran Legislation, the promise of buying and selling is regulated by the Civil Code in the Art.1570, in which there are mentioned several circumstances that must be fulfilled for its validity, the regulation is complemented with the general law of the contract, established in the Art. 1460 and 1461, relating to the contract’s elements, capacity and assent. Inside the Civil Ecuadoran Code, exist several elements that were not included and there result to be transcendental for the validity and efficiency of the promise of buying and selling, which will be mentioned later: In the Civil Code a clear and specifies regulations does not exist about the promise of buying and selling, we can observe that the level of contract is not specified, a certain definition does not exist; some circumstances are established as essential for the validity, but exist others that were not included for example: the price, form of payment, the term and the penalization. The same ones that is fundamental for guaranteeing the fulfillment of the principal obligation that is the contract of buying and selling in the future. The promise by third person as valid, is included in the Civil Code when exists a ratification, which turns out to be harmful for the private property and cause a prejudice for buyers of good faith. Exists an element that does not include in the Civil Ecuadoran Code and it would be very useful to guarantee the property of the real estate, the certificate of property granted by the Register of the Property The observations are directed in order that the promise of buying and selling offers to the contracting party a real guarantee and efficiency in the moment to sign the contract of buying and selling